Ameliorative effect of carnosine and N‐acetylcysteine against sodium nitrite induced nephrotoxicity in rats. Issue 5 (28th October 2018) - Ansari, Fariheen Aisha; Khan, Aijaz Ahmed; Mahmood, Riaz
Abstract: The widespread use of sodium nitrite (NaNO2 ) for various industrial purposes has increased human exposure to alarmingly high levels of nitrate/nitrite. Because NaNO 2 is a strong oxidizing agent, induction of oxidative stress is one of the mechanisms by which it can exert toxicity in humans and animals. We have investigated the possible protection offered by carnosine (CAR) and N‐acetylcysteine (NAC) against NaNO 2 ‐induced nephrotoxicity in rats. Animals orally received CAR at 100 mg/kg body weight/d for seven days or NAC at 100 mg/kg body weight/d for five days followed by a single oral dose of NaNO 2 at 60 mg/kg body weight. The rats were killed after 24 hours, and the kidneys were removed and processed for various analyses. NaNO 2 induced oxidative stress in kidneys, as shown by the decreased activities of antioxidant defense, brush border membrane, and metabolic enzymes. DNA‐protein crosslinking and DNA fragmentation were also observed. CAR/NAC pretreatment significantly protected the kidney against these biochemical alterations. Histological studies supported these findings, showing kidney damage in NaNO 2 ‐treated animals and reduced tissue impairment in the combination groups. The protection offered by CAR and NAC against NaNO 2 ‐induced damage, and their nontoxic nature, makes them potential therapeutic agents against nitrite‐induced nephrotoxicity. Abstract : Carnosine and N‐acetylcysteine protect rat kidney cells against sodium nitrite–induced oxidative stress and damage. Significant protection was observed in various parameters that were analyzed, including DNA damage studies and metabolic and anatomical alterations. This, in addition to their nontoxic nature, makes them potential therapeutic agents to attenuate nitrite‐induced nephrotoxicity.